Antilisterial effect of citrus essential oils and their performance in edible film formulations. (January 2016) - Randazzo, Walter; Jiménez-Belenguer, Ana; Settanni, Luca; Perdones, Angela; Moschetti, Marta; Palazzolo, Eristanna; Guarrasi, Valeria; Vargas, Maria; Germanà, Maria Antonietta; Moschetti, Giancarlo
Abstract: The antimicrobial activity of eight essential oils (EOs) extracted from the fruit peel of Citrus genotypes (orange, mandarin and lemon) was evaluated against 76 strains of Listeria monocytogenes, previously isolated from different food matrices. EOs showing the most (EO L2 and EO L8) and least (EO O3 and EO M7) effective inhibition activities were chemically characterized by gas chromatography coupled with mass spectrometry (GC/MS) to compare their composition. EO L2 and EO L8 were chosen to determine the MIC and to evaluate the cell viability of the most sensitive strains ( L. monocytogenes LM35 and LM69) after 1, 2, 4 and 6 h of exposure. The effectiveness of chitosan (CH) and methylcellulose (MC) edible films, alone and in combination with EO L2 and EO L8, was determined against LM35 and LM69 at 37 °C for 0, 8 and 24 h and at 8 °C for 0, 1, 3 and 7 days. In addition, the analysis of the microstructure of the films were performed by scanning electron microscope (SEM) to evidence the interactions between the polymers and EOs. Thirty-five and twenty-nine strains were clearly inhibited by EO L2 and EO L8, respectively, while the other Citrus EOs showed poor (EO M1, O4, O5, O6) or minimal (EO O3 and M7) antimicrobial activity. A total of 36 chemical volatile substances was identified by GC/MS to detect the compounds that might play an important role in the characterization of the EOs. The chemical characterization points to oxygenated monoterpenes as relevant compounds in inhibiting Listeria strains, since they have been detected in lemon EOs in concentrations four/five folds higher than orange EOs. Generally, CH- and MC-based films containing EO L2 and EO L8 showed antilisterial activities, even though, the best performances were observed in case of CH-films at 8 °C, with a major reduction up to 3 log (CFU/cm 2 ) in case of EO L2 incorporation. The microstructures observed by SEM suggested a better incorporation of the EOs in CH matrix, where a higher amount of oil droplets was distinguished. Therefore, lemon EOs incorporated into chitosan films could be an efficient tool to control Listeria monocytogenes, especially in refrigerated applied conditions. Highlights: Citrus essential oils inhibited several Listeria monocytogenes of food origin. Lemon EOs showed the most consistent inhibitory activities. Oxygenated monoterpenes were implicated in the process of bacterial inhibition. EOs were active after incorporation into edible film formulation. Chitosan based-films were applicable for food biopreservation.